Predictive factors for extrahepatic recurrence of hepatocellular carcinoma following liver transplantation. Issue 7 (20th May 2016) - Andreou, Andreas; Bahra, Marcus; Schmelzle, Moritz; Öllinger, Robert; Sucher, Robert; Sauer, Igor M.; Guel‐Klein, Safak; Struecker, Benjamin; Eurich, Dennis; Klein, Fritz; Pascher, Andreas; Pratschke, Johann; et al.
Abstract: Background: Recurrence of hepatocellular carcinoma (HCC) in patients treated with liver transplantation (LT) is associated with diminished survival. Particularly, extrahepatic localization of HCC recurrence contributes to poor prognosis. Patients and methods: Clinicopathological data of patients who underwent LT for HCC between 1989 and 2010 in a high‐volume transplant center were retrospectively evaluated, and predictors of extrahepatic recurrence were identified. Results: Three hundred and sixty‐four patients underwent LT for HCC. After a median follow‐up time of 78 months, 93 patients (25%) were diagnosed with a recurrence. Median time to recurrence was 19 months. Recurrence was located exclusively in the liver in 19 cases (20%), and 74 patients (80%) had extrahepatic recurrence. Factors associated with extrahepatic recurrence in multivariate analysis included HCC beyond the Milan criteria (p < 0.0001) and the presence of macrovascular tumor invasion (p = 0.035). In patients with HCC beyond the Milan criteria who developed a recurrence (N = 73), macrovascular invasion was the only positive predictor of extrahepatic recurrence in multivariate analysis (p < 0.0001). In patients with HCC within the Milan criteria who recurred after LT (N = 20), DNA‐index >1.5 (p = 0.013) was the only predictive factor for extrahepatic recurrence in multivariate analysis. Conclusions: Advanced HCC beyond the Milan criteria and the presence of macrovascular invasion are associated with an increased risk for extrahepatic recurrence and are currently considered as relative contraindications to LT. In patients with HCC within the Milan criteria, the DNA‐index represents a valuable prognostic marker for the development of extrahepatic recurrence and may support the selection of patients for intensified postoperative tumor surveillance.